The growth of non-manual workers' unions in manufacturing industries in Great Britain since 1948 - Bain, G; Bain, George Sayers (1968)
﻿ This study attempts to discover the major factors which promote or hinder the growth of trade unionism among white-collar workers, particularly those employed in manufacturing Industries, in Great Britain. Chapter I simply discusses the reasons for undertaking such a study, a few of the methodological and conceptual problems which arise, as well as the nature of the techniques and the analytical framework used in the study. Chapter II is concerned with the pattern of white-collar employment in Britain and reveals how the composition of the labour force is changing. Already almost four out of ten workers are white-collar employees, and it is probable that by the 1980's they will outnumber the manual workers. Clearly, if the trade union movement is to continue as a dynamic and effective force in British society, it must recruit these white-collar workers. The extent to which the trade union movement has already done this is considered in Chapter III. In particular, it assembles the data on the dependent variable of this study - the occupational and industrial pattern of white-collar unionism in Britain. The pattern reveals that there are considerable variations in the degree of white-collar unionism from one industry and occupation to another. All the remaining chapters analyse the factors which this study considers worthy of examination in searching for an explanation of this pattern. Chapter IV considers the socio-demographie characteristics of white-collar workers. Chapter V examines the white-collar workers' economic position, while Chapter VI analyses their work situation. The role which trade unions and employers play in union growth is explored in Chapters VII and VIII respectively, while the influence of the government and the social climate is investigated in-Chapter IX, Chapter X draws the various parts of the analysis together and tries to produce a few generalisations regarding the growth of white-collar unionism. The gist of these chapters can be briefly summarised. No significant relationship was found between the aggregate pattern of white-collar unionism and any of the following factors: (a) such socio-demographic characteristics of white-collar workers as their sex, social origins, age, and status; (to) such aspects of their economic position as earnings, other terms and conditions of employment, and employment security; (e) such aspects of their work situation as the opportunities for promotion, the extent of mechanisation and automation, and the degree of proximity to unionised manual workers; and (d) such aspects of trade unions as their public image, recruitment policies, and structures. While the evidence regarding some of these factors was not sufficiently reliable to permit them to be discounted completely, it was satisfactory enough to reveal that at most they have been of negligible importance. But the gist of these chapters is not entirely negative. The aggregate pattern of white-collar unionism was found to be significantly related to the following factors: employment concentration, union recognition, and government action. The relationship between these key independent variables and between them and the dependent variable can be usefully summarised in a two-equation descriptive model. D = f (C,E) (1) R = g (D,G) (2) where D = the density of white-collar unionism; C = the degree of employment concentration; R = the degree to which employers are prepared to recognise unions representing white-collar employees; and G = the extent of government action which promotes union recognition. The first equation specifies that the density of white-collar unionism is a function of the degree of employment concentration and the degree to which employers are prepared to recognise unions representing white-collar employees. The more concentrated their employment the more likely employees are to feel the need to join trade unions because of "bureaucratisation", and the more easily trade unions can meet this need because of the economies of scale characteristic of union recruitment and administration While employment concentration is a necessary condition for the growth of white-collar unions, it is not a sufficient condition. Employers must also be prepared to recognise these unions. The greater the degree to which employers are prepared to do this the more likely white-collar employees are to join unions. For they are less likely to Jeopardise their career prospects by joining, they can more easily reconcile union membership with their "loyalty" to the company, and they will obtain a better service because their unions will be more effective in the process of job regulation. The first independent variable makes white-collar employees predisposed towards trade unions, while the second makes union membership practical and attractive. But the degree to which employers are prepared to recognise unions representing white-collar employees is to some extent dependent upon the membership density of these unions. This is why the second equation is necessary. It specifies that the degree of recognition is a function of the density of white-collar unionism and the extent of government action which promotes union recognition. Employers generally do not concede recognition to a union before it has at least some membership. The only exception to this is when employers recognise a union prior to it having obtained any membership in order to encourage its growth at the expense of other "less desirable" unions. Even in these cases, recognition is at least partly a function of membership density - that of the "less desirable" unions* But while a certain density of membership is a necessary condition for any degree of recognition to be granted, the findings of this study suggest that it is generally not a sufficient condition. The industrial strength of white-collar unions, as determined by the size of their membership and their willingness and ability to engage in industrial warfare, has generally not been sufficient in itself to force employers to concede recognition. This has also required the introduction of government policies which have made it easier for unions to exert pressure for recognition and harder for employers to resist it. The model is claimed to give an adequate explanation of the growth of aggregate white-collar unionism in Britain, and, in addition, to have some important implications for research on this subject as well as for the function of unions in modern industrial society, and the future growth of white-collar unionism.